High-temperature nitridation and oxidation of Ti-based alloys - Thongtem S. (2014)
High-temperature nitridation in nitrogen followed by oxidation in air of Ti-(0.5-20.0)wt.%V and Ti-36.0wt.%Al were studied at 1100-1300 K. The oxidation rate of Ti-(0.5-20.0)wt.%V over 5 h continuously increased with the concentration of vanadium up to 10.0 wt.% V. Above this level, the oxidation rate tended to be constant when the experimental time was sufficient. However, the lowest oxidation rate was found in the case of Ti-36.0wt.%Al. Nitridation can effectively protect the alloys against oxidation. The alloys were characterized by x-ray diffraction and the results were in agreement with those characterized by a CHNS/O analyser. In addition, the characteristics of the alloys revealed by SEM micrographs were consistent with the oxidation rates in air. Copyright © 2001 John Wiley & Sons, Ltd.